-4(4y-1)+6y=6y+12

Simple and best practice solution for -4(4y-1)+6y=6y+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(4y-1)+6y=6y+12 equation:


Simplifying
-4(4y + -1) + 6y = 6y + 12

Reorder the terms:
-4(-1 + 4y) + 6y = 6y + 12
(-1 * -4 + 4y * -4) + 6y = 6y + 12
(4 + -16y) + 6y = 6y + 12

Combine like terms: -16y + 6y = -10y
4 + -10y = 6y + 12

Reorder the terms:
4 + -10y = 12 + 6y

Solving
4 + -10y = 12 + 6y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6y' to each side of the equation.
4 + -10y + -6y = 12 + 6y + -6y

Combine like terms: -10y + -6y = -16y
4 + -16y = 12 + 6y + -6y

Combine like terms: 6y + -6y = 0
4 + -16y = 12 + 0
4 + -16y = 12

Add '-4' to each side of the equation.
4 + -4 + -16y = 12 + -4

Combine like terms: 4 + -4 = 0
0 + -16y = 12 + -4
-16y = 12 + -4

Combine like terms: 12 + -4 = 8
-16y = 8

Divide each side by '-16'.
y = -0.5

Simplifying
y = -0.5

See similar equations:

| 240+.25x=440 | | 220+.25x=420 | | 2x-45=60 | | 3v-3-7=-4(-5v+2)-7v | | 524/5-3 | | 0=60-.01x | | 3x-8+2(5x+4)=-2(x+3) | | -3/8+5/8 | | 25=60-.01x | | x^2+8x-201=0 | | x^2+8x=201 | | 2(x-2)=5x+4-2(-6x-1) | | 0.10p+0.05=20 | | 230+.15x=420 | | 2x-4=5x+4-12x-2 | | (-12.8)/(-0.8) | | 4x+2=6x-30 | | 3b+12=5b-40 | | 2/5(5w+10) | | -6(-4)-3y=39 | | x=4+13 | | 7r-5r+2r=5r-r | | 4+4r-1=7r+7-2r | | x=-21+16 | | 50=14+2x | | 4x+2=6x+30 | | -7a-15+-4a+18= | | 4v+24=-3(6v-6)+4v | | 5/4(8) | | 3(-6)+6=2(-6) | | 3p+11p=28 | | 5x-6x=8-2x |

Equations solver categories